METHODOLOGY FOR CREATING DATA VISUALIZATION. A CASE STUDY FOR INTERDISCIPLINARY TIMELINES BETWEEN 1750-1900 - PUȘCAȘIU, Voica (Studia Universitatis Babeș-Bolyai Digitalia, 2018)
The present study was originally aimed at creating a helping tool for teaching and understanding art history through the use of visual schemes. Despite the fact that timelines are often present in both history and art history books their status is rather that of footnotes (Wolf, Gombrich 656-663, * * * 392-395) and a study for their methodology and usage was truly lacking. Considering the way in which simple data visualization can comprise vast amount of information and deliver it in an efficient manner, it makes it worthwhile to ensure its scientific quality and accuracy through proper methods, as well as to actually creating ones that are both simple and eye-catching. Thus this paper is a result of a personal interest in the development of such tools and the challenges encountered along the way. Offering valuable information in a short glimpse through simple graphics over the life and the artistic creation of various artists is only enhanced by the opportunities provided by digital tools and the virtual environment, so it is perhaps an auspicious time to start seriously considering this type of research.